2013
DOI: 10.22564/rbgf.v31i4.339
|View full text |Cite
|
Sign up to set email alerts
|

Processing of High-Resolution, Shallow Seismic Profiles, Guanabara Bay – Rio De Janeiro State, Brazil

Abstract: ABSTRACT. This paper presents a proposal for implementing a processing flowchart for high-resolution single-channel seismic data acquired in Guanabara Bay, followed by its interpretation. Geologically, it consists of mapping the Guanabara Bay Quaternary deposits relative to the drowning of a fluvial paleochannel that resulted from recent sea level changes. So far, high-resolution seismic data have been interpreted without any signal improvement, while the development of a processing flowchart for this is hardl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…In Brazil, several seismic studies have been conducted in areas of bays, lakes, rivers, and estuaries (Quaresma et al, 2000;Catanzaro et al, 2004;Hatushika et al, 2007;Paolo & Mahiques, 2008;Veronez Jr et al, 2009a, 2009bQuaresma et al, 2011;Marino et al, 2013;Silva et al, 2014;Barros et al, 2017). These research works have identified and classified echo-characters and sonographic patterns, which can be defined according to their reflection patterns (seismic facies).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, several seismic studies have been conducted in areas of bays, lakes, rivers, and estuaries (Quaresma et al, 2000;Catanzaro et al, 2004;Hatushika et al, 2007;Paolo & Mahiques, 2008;Veronez Jr et al, 2009a, 2009bQuaresma et al, 2011;Marino et al, 2013;Silva et al, 2014;Barros et al, 2017). These research works have identified and classified echo-characters and sonographic patterns, which can be defined according to their reflection patterns (seismic facies).…”
Section: Introductionmentioning
confidence: 99%
“…Na maioria dos casos, o processamento é realizado com aplicativos proprietários, os quais incluem apenas rotinas básicas de processamento sem a aplicação de técnicas mais avançadas de processamento (Henriet et al, 1978;Berryhill et al, 1986;Lee et al, 2004). Por outro lado, trabalhos como os de Barclay (1993), Duchesne e Bellefleur (2007), Siyou et al (2009), Gomes et al (2011) e Marino et al (2013) utilizaram as técnicas rotineiramente empregadas pela indústria do petróleo no processamento de linhas sísmicas de alta resolução.…”
Section: Introductionunclassified